2019
DOI: 10.21565/ozelegitimdergisi.467417
|View full text |Cite
|
Sign up to set email alerts
|

Özel Gereksinimli Çocuğa Sahip Ebeveynlerin Sosyal Destek Algılarının ve Yılmazlık Düzeylerinin İncelenmesi

Abstract: Bu araştırma özel gereksinimli çocuğa sahip ebeveynlerin sosyal destek algılarının ve yılmazlık düzeylerinin çeşitli değişkenler açısından incelenmesi amacıyla yapılmıştır. Betimsel araştırma yöntemlerinden ilişkisel tarama modeli kullanılarak desenlenen araştırmanın çalışma grubunu özel gereksinimli çocuğa sahip 128 anne ve 34 baba oluşturmaktadır. Veri toplama aracı olarak Kişisel Bilgi Formu, "Yenilenmiş Anne-Baba Sosyal Destek Ölçeği" ve "Aile Yılmazlık Ölçeği" kullanılmıştır. Verilerin analizinde T-Testi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
3
0
4
Order By: Relevance
“…There were various results in the literature parallel to the results of the present study. In a study conducted by Aysever & Demirok (2019), there were significant differences in the Bellicosity subdimension of the Family Resilience Assessment Scale. Kumbasar (2016) found significant differences in the Self-Efficacy subdimension of the scale in favor of the mother.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There were various results in the literature parallel to the results of the present study. In a study conducted by Aysever & Demirok (2019), there were significant differences in the Bellicosity subdimension of the Family Resilience Assessment Scale. Kumbasar (2016) found significant differences in the Self-Efficacy subdimension of the scale in favor of the mother.…”
Section: Discussionmentioning
confidence: 95%
“…When the resilience levels of parents were evaluated in terms of the age variable, the resilience levels of young parents were higher in the self-efficacy subdimension. In their studies, Aysever & Demirok (2019) found that young parents were more resilient in the control subdimension of the scale, Kaner et al (2011) found that they were more resilient in the self-efficacy and commitment to life subdimensions. Similarly, according to Lee et al (2009), young parents perceive themselves as being more resilient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ebeveynlerin çocuk sahibi olmaya karar vermesi, onların hayatlarında önemli bir dönüm noktası olup birçok değişikliği ve yeniliği beraberinde getirmektedir. Ebeveynler, dünyaya gelecek çocuklarının normal gelişim göstermesini beklemekte ve çoğu zaman özel gereksinimi olan bir çocuğa sahip olabileceklerini düşünmemektedirler (Aysever & Demirok, 2019). Psikolojik sağlamlık, bir bireyin stresli yaşam olayları ve zorluklarla karşılaştığında, (yaralanma, tehditler ve önemli stres kaynakları) istikrarlı psikolojik ve fiziksel işleyişi nispeten sürdürme veya psikolojik durumunu eski olumlu haline getirme yeteneği olarak ifade edilmektedir (Seiler & Jenewein, 2019).…”
Section: Geni̇şleti̇lmi̇ş öZetunclassified
“…This period brings many changes and new things with it. Parents expect their future children to show a healthy development, and often do not think that they may have a child with special needs (Aysever & Demirok, 2019). When parents learn that their children have special needs, they may experience such feelings as deep sadness, guilt, sinfulness, regret, being tested, anxiety and anger.…”
mentioning
confidence: 99%